1988
DOI: 10.1079/bjn19880039
|View full text |Cite
|
Sign up to set email alerts
|

Leucine degradation in sheep

Abstract: 1. In vitro leucine catabolism in adipose tissue, skeletal muscle, kidney and liver homogenates was studied in sheep.2. In Expt 1, Suffolk × Targhee ram lambs were slaughtered at 1, 28, 56, 84, 112, 140, 168, 196, 224 and 365 d of age. In Expt 2, 5-month-old crossbred wethers were fed on 80, 120 or 180 g crude protein (nitrogen × 6·25) /kg diets for 4 weeks or fed on 120 g crude protein/kg for 4 weeks and then fasted for 48 or 96 h before slaughter. Leucine catabolism was assayed in tissue homogenates for Expt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 19 publications
2
11
0
Order By: Relevance
“…The mRNA abundance of BCATm was greatest in both scAT and vAT compared with all other tissues, which indicates that, on a transcriptional level, AT might be an important contributor in the initiation of BCAA catabolism in dairy cattle. This notion is in line with a study by Bergen et al (1988), who showed that Leu deamination activity as well as the predicted deamination capacity based on body and tissue weights was highest in scAT compared with muscle, liver, and kidney of mature sheep. More recently, Green et al (2016) demonstrated the importance of BCKA oxidation in adipogenic differentiation and that inhibition of BCAA catabolism compromised adipogenesis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The mRNA abundance of BCATm was greatest in both scAT and vAT compared with all other tissues, which indicates that, on a transcriptional level, AT might be an important contributor in the initiation of BCAA catabolism in dairy cattle. This notion is in line with a study by Bergen et al (1988), who showed that Leu deamination activity as well as the predicted deamination capacity based on body and tissue weights was highest in scAT compared with muscle, liver, and kidney of mature sheep. More recently, Green et al (2016) demonstrated the importance of BCKA oxidation in adipogenic differentiation and that inhibition of BCAA catabolism compromised adipogenesis.…”
Section: Discussionsupporting
confidence: 91%
“…Even if full hepatic BCKA oxidation may be relatively low, high BCKDH activity would ensure the removal of excess BCKA, which are toxic at high blood concentrations. In general, it has been acknowledged that the initial step in BCAA catabolism, the reversible deamination via BCAT, may occur extrahepatically [e.g., in muscle (Bequette et al, 2002), AT (Bergen et al, 1988), or MG (Bequette et al, 1996a)]. Depending on the tissue, this is followed by either the export of the resulting BCKA into the blood stream or direct oxidative decarboxylation of BCKA to acyl-CoA derivatives via BCKDH and, hence, not adding to the plasma flux .…”
Section: Discussionmentioning
confidence: 99%
“…Leucirze oxidation. The liver is the major site of catabolism for most amino acids but substantial oxidative capacity for the branched-chain amino acids (leucine, isoleucine and valine) resides also in ovine skeletal muscle and adipose tissue (Goodwin et al 1987;Bergen et al 1988), which contain both the transaminase and the branched-chain 0x0-acid dehydrogenase. The activity of the dehydrogenase is tightly regulated by the phosphorylation status; the phosphorylated form is inactive and the dephosphorylated is active (Randle et a/.…”
Section: Whole-animal Kineticsmentioning
confidence: 99%
“…Another difference between ruminants and monogastrics is in the developmental expression of BCAT in ruminants. Sheep BCAT activity declines throughout development, from fetus to ruminant, especially in skeletal muscle [11,13,14,29]. Such a decrease in BCAT expression during development has not been described in any other species [31].…”
Section: Resultsmentioning
confidence: 99%
“…We have shown previously that BCAT activity is very low in preruminant lamb tissues [11]. Studies carried out at other developmental stages (fetus, growing lambs, adults and pregnant ewes) confirm that BCAT activity is lower in sheep than in rat tissues, and indicate that BCAT activity decreases during development [13,14]. As the BCAT isoenzymes have not yet been purified from sheep, the biochemical basis for the differences between ruminants and monogastrics is not known.…”
mentioning
confidence: 99%